Married to Intolerance: Attitudes toward Intermarriage in Germany, 1900–2006 - Voigtländer, Nico; Voth, Hans-Joachim (American Economic Review, 2013)
We analyze under what conditions intermarriage can be used as an indicator of tolerance, and whether such tolerant attitudes persisted in Germany during the twentieth century. We find strong evidence for the persistence of tolerant attitudes towards intermarriage with Jews. At the same time, our empirical analysis also cautions against using intermarriage as a simple proxy for tolerance: The size of Jewish communities in the early twentieth century is an important confounding factor.